EXPLORING CAUSE OF MISCONCEPTION ON REACTION RATE USING 4TMC DIAGNOSTIC TEST INSTRUMENT - Ilham Pradana Putra Harahap; Dian Novita; Rezi Ulya Fauziah; Chawalluck Sriwarom (JPPS (Jurnal Penelitian Pendidikan Sains), 2021)
The research purpose is to explore the cause of misconception on the factors affecting reaction rates using the 4TMC diagnostic test instrument which is reported on the students' conceptions profile,  students' misconceptions,  and the causes of students' misconceptions. This research was conducted at the class XI science three students senior high school. The result showed that (1) the students’ conceptions profile on the factors affecting reaction rates is 49.77 % misconceptions, 29.55 % did not understand the concept, and 20.68 % understood the concept, (2) the students' misconceptions profile of each sub-material ie misconception of concentration 24.20 %, temperature 21.00 %, surface area 26.03 % and catalyst 28.77 % and there is 5 student (22.73 %) included in the category of high misconceptions, 13 students (59.09 %) medium misconceptions and 4 students (18.18 %) low misconceptions, (3) students’ misconceptions depend on a variety of causes, ie: associative thinking 43.53 %, incomplete reasoning 24.02 %, preconceptions 19.84 %, incorrect intuition 9.96 %, humanistic thinking 2.65 %.